The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/biology10090862
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis and Genetic Diversity of Colletotrichum falcatum Isolates Causing Sugarcane Red Rot Disease in Bangladesh

Abstract: Colletotrichum falcatum Went causes red rot disease in sugarcane farming in the tropical and sub-tropical regions. This disease causes significant economic loss to the sugarcane production industry. Successful disease management strategies depend on understanding the evolutionary relationship between pathogens, genetic diversity, and population structure, particularly at the intra-specific level. Forty-one isolates of C. falcatum were collected from different sugarcane farms across Bangladesh for molecular ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Appressoria and perithecia were not observed. The morphological characteristics observed for C. falcatum strains aligned with those formerly described by Costa et al [22] and Hossain et al [50]. Similarly, the specific characteristics of T. paradoxa strains resembled those in the description of the pathogen in the CABI Compendium [28].…”
Section: Detection Of Pathogens Associated With Sugarcane Stalk Inter...supporting
confidence: 85%
“…Appressoria and perithecia were not observed. The morphological characteristics observed for C. falcatum strains aligned with those formerly described by Costa et al [22] and Hossain et al [50]. Similarly, the specific characteristics of T. paradoxa strains resembled those in the description of the pathogen in the CABI Compendium [28].…”
Section: Detection Of Pathogens Associated With Sugarcane Stalk Inter...supporting
confidence: 85%
“…The coefficient of genetic differentiation (GST) at population level was estimated as GST = ( H T − H S )/H T , where H T corresponds to the total gene diversity, and H S corresponds to the gene diversity within sub-populations [ 51 , 52 ]. Gene flow is defined as the average per generation of migrants transferred across populations and it is estimated indirectly based on the formula: Nm = 0.5 (1 − GST)/GST [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…A previous report showed that C. fructicola is a non-host-specific pathogen infecting fruit, vegetables, and economic crops, including apple (Malus pumila) [37], sugarcane (Saccharum officinarum) [38], blueberry (Vaccinium corymbosum) [53], and Camellia yuhsienensis [54]. C. fructicola was described as a common species existing on the leaves of tea-oil camellia [35].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, C. siamense showed broad variation in cultural appearance [21]. Although 11 isolates of Colletotrichum Group 2 and six isolates of Colletotrichum Group 4, isolated from different locations, were slightly different on the morphology of colony and conidia, they were all identified to be the species of C. siamense by phylogenetic analyses, which showed the unreliability and inconsistency of Colletotrichum identification methods relying only on colonial and morphological characteristics because fungal colony and morphological characteristics are affected by environmental factors [38]. In the present study, a new Colletotrichum species, C. cordylinicola, was reported causing anthracnose on tea-oil camellia in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation